Evaluating the Distribution of Educational Services Using GIS: A Case Study of Kut City, Iraq - Kareem Khlaif, Rusul; Sabah Jaber, Hussien (Journal of Planner and Development, 2024)
Iraq's education system has been facing significant challenges in providing quality educational services, particularly for schools. The most important of these challenges are the number of schools, their distribution, and the difficulty of  reaching schools by students.  The assessment and analysis of spatial patterns play a crucial role in enhancing the accessibility and quality of education using Geographic Information System (GIS). Spatial and attribute data of  schools were collected by Wasit Education Directorate using GPS. Spatial analysis techniques were utilized for primary and secondary schools in Kut city/ Iraq , including  kernel density and Moran's I. Kernel density values indicated primary school concentrations up to 91,660 in Kut district and secondary concentrations up to 79,879 in Kut. Moran's I detected no significant spatial autocorrelation for any schools. The results exposed considerable gaps in educational access and highlighted uneven, inequitable distribution of schools across Kut city. The techniques used offer valuable quantitative insights to inform evidence-based planning and policymaking.